2021
DOI: 10.1002/adfm.202104696
|View full text |Cite
|
Sign up to set email alerts
|

Materials Informatics Reveals Unexplored Structure Space in Cuprate Superconductors

Abstract: High-temperature superconducting cuprates have the potential to be transformative in a wide range of energy applications. In this work, the corpus of historical data about cuprates is analyzed using materials informatics, re-examining how their structures are related to their critical temperatures (Tc). The available data is highly clustered and no single database contains all the features of interest to properly examine trends. To work around these issues a linear calibration approach that allows the utilizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…This, coupled with the solid-state literature and nascent Inorganic Crystal Structure Database, resulted in a host of experiments targeted at potential novel materials that were both feasible and unreported. More recently, ML-based approaches have been applied to better explore the space of cuprate-like compounds. , However, even simple database queries and linear regressions (combined with DFT estimates of stability) suffice to identify potential compounds that fill-in the gaps in the distribution of observed apical and in-plane Cu–O distance distributions for this class of compounds …”
Section: Recommendations Toward ML For Exceptional Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…This, coupled with the solid-state literature and nascent Inorganic Crystal Structure Database, resulted in a host of experiments targeted at potential novel materials that were both feasible and unreported. More recently, ML-based approaches have been applied to better explore the space of cuprate-like compounds. , However, even simple database queries and linear regressions (combined with DFT estimates of stability) suffice to identify potential compounds that fill-in the gaps in the distribution of observed apical and in-plane Cu–O distance distributions for this class of compounds …”
Section: Recommendations Toward ML For Exceptional Materialsmentioning
confidence: 99%
“…186,187 However, even simple database queries and linear regressions (combined with DFT estimates of stability) suffice to identify potential compounds that fill-in the gaps in the distribution of observed apical and inplane Cu−O distance distributions for this class of compounds. 188 Alternatively, one can focus on previously unobserved outcomes. The information entropy of the observed property distribution can be useful for identifying outcome imbalances, and active learning used to prioritize new samples to correct these imbalances, recently demonstrated in the context of formation energy/structure biases of intermetallic compounds.…”
Section: Vc Sample What Can Be Made and How To Make It � Defer Optimi...mentioning
confidence: 99%
“…License: CC BY-NC-ND 4.0 identify potential compounds that fill-in the gaps in the distribution of observed apical and in-plane Cu-O distance distributions for this class of compounds. 188 Alternatively, one can focus on previously unobserved outcomes. The information entropy of the observed property distribution can be useful for identifying outcome imbalances, and active learning used to prioritize new samples to correct these imbalances, recently demonstrated in the context of formation energy/structure biases of intermetallic compounds.…”
Section: Try To Fill-in-the-blanks Of Input and Output Spacementioning
confidence: 99%
“…Materials informatics has shown that the cuprate class of superconductors contains a highly unexplored materials space that has yet to be explored [18]. This is why formulae from the SuperCon database are used for the training of our model.…”
Section: A Datamentioning
confidence: 99%